Platelet spleen tyrosine kinase is a key regulator of anti-PF4 antibody–induced immunothrombosis - Jan Zlamal; Vera M. Ripoll; Christine S.M. Lee; Filip Toma; Karina Althaus; Flavianna Rigoni; Andreas Witzemann; Shane Whittaker; David Capraro; Günalp Uzun; Tamam Bakchoul; Vivien M. Chen (Blood Advances)
Abstract: Vaccine-induced immune thrombotic thrombocytopenia (VITT) is a rare but serious prothrombotic adverse event after vaccination with adenovector-based COVID-19 vaccines. Laboratory findings indicate that anti–platelet factor 4 (PF4) immunoglobulin G antibodies are the causing factor for the onset of thromboembolic events in VITT. However, molecular mechanisms of cellular interactions, signaling pathways and involvement of different cell types in VITT antibody–mediated thrombosis are not fully understood. Moreover, uncertainty exists regarding current treatment protocols because the sole anticoagulation was shown to be inefficient to prevent thrombosis progression in severe VITT cases. In this study, we demonstrate that platelet spleen tyrosine kinase (SYK) modulates anti-PF4 VITT-mediated thrombus formation in an ex vivo model of immunothrombosis. Our study showed that the selective inhibition of SYK can abrogate VITT antibody–driven procoagulant platelet formation, activation of plasmatic coagulation as well as platelet-leukocyte interplay. Most importantly, the specific inhibition of SYK in platelets but not in neutrophils prevented VITT antibody–induced multicellular thrombus formation, without perturbing the platelet function. Our findings indicate that the specific targeting of platelet SYK might be a promising therapeutic approach to prevent thrombotic complications in patients with antibody-mediated immunothrombosis.